Evaluation of Performance Against Contractors’ Tender Position on Selected Public Construction Projects - Salla, D. E.; Bustani, S. A.; Dahiru, A.; Awalu, A. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Previous studies have investigated tendering of construction projects and project performance in silos. This study examines project performance of contractors, based on their tender positions as perceived by clients. Quality and speed of delivery of construction projects formed the study remit. A questionnaire was administered to selected public clients (Federal Ministries and Departments). Responses received were analyzed with aid of simple means and percentages. The analysis showed that 76.92% of tenders submitted were below the mean tender sum. Similarly, 23.08% of the tenders were above the mean Tender sum. Further examination revealed that 23.08% of projects were completed at costs significantly higher than the original contract price. Accordingly, 80.77% of the contractors delivered their projects within the contract price. Inadvertently, clients’ rating of the performance of contractors showed that their projects were delivered within budget at final accounts, with performances below average as Clients disapproved the quality and speed of delivery by such contractors. On the other hand, contractors whose projects overran their budgets were rated above average in terms of performance and delivery quality. The mean tender sum was recommended as the most important benchmark for clients in early projects decision at tender.